Study of arbuscularmycorrhizal association in some medicinal herbs of acanthaceae family from darjeeling district, West bengal, India - TAMAL MONDAL; SIKHA DUTTA (International Journal of Pharma and Bio Sciences, 2017)
A survey was carried out to determine the arbuscular mycorrhizal status in some common medicinal herbs of Acanthaceae family like, Andrographis paniculata (Burm.f.) Wall.ex Nees, Hygrophila auriculata (Schumacher) Heine, Barleria lupulina Lindley, Justicia adhatoda L. From Grid-line intersect method it was evidenced that all the plants under investigation were colonized by the arbuscular mycorrhizal fungi as arbuscules were present in the roots. The percentage of mycorrhizal colonization was highest in the roots of Barleria lupulina Lindley (49.5%), followed by Hygrophila auriculata (Schumacher) Heine (27%), Andrographis paniculata (Burm.f.) Wall.ex Nees (21%), and lowest in Justicia adhatoda L. (14%). Variations noticed in root infection and spore density were statistically considerable. The arbuscular mycorrhizae fungi (AM) which were observed in the current study typically belong to the genus Glomus.